Bridge control of photophysical properties in benzothiazole-phenoxazine emitters – from thermally activated delayed fluorescence to room temperature phosphorescence. Issue 12 (13th January 2022) - Paredis, Simon; Cardeynaels, Tom; Deckers, Jasper; Danos, Andrew; Vanderzande, Dirk; Monkman, Andrew P.; Champagne, Benoît; Maes, Wouter
Abstract : Three phenoxazine-π-bridge-benzothiazole dyes are investigated by a joint experimental-computational approach. Depending on the linker, TADF or RTP (also in solution) is observed. Abstract : The bridging phenyl group in a fluorescent phenoxazine-benzothiazole donor–acceptor dyad is replaced by either a naphthalene or a thiophene moiety to probe the influence of a more extended conjugated system or the presence of a sulfur-containing heteroaromatic spacer on the emissive properties. These seemingly small structural alterations strongly affect the relative positions of the excited states, the fluorescence intensity, and the emission mechanism. Consequently, thermally activated delayed fluorescence (TADF) is observed at longer timescales for the materials with phenyl and naphthalene linkers, whereas the thiophene group promotes room temperature phosphorescence (RTP), both in the solid state and in solution, and enhances singlet oxygen generation. Phosphorescence in solution at ambient temperature from a purely organic molecule without heavy halogen functionalisation is quite rare, and this unique property calls for further specific attention.